The Dividend Decision Influence on Share Price Movements in Developing Economics - Khatiwada, Atmaram (INTELLIGENCE Journal of Multidisciplinary Research, 2026)
This paper discusses the impact of dividend policy on the share-price behaviour in the developing economy of Nepal, considering the effects of dividend per share (DPS) and dividend payout ratio (DPR) on the annual changes in the price per share in the market ( ΔMPS) and share-price volatility (VOL) with the moderating influence of macroeconomic factors, i.e., inflation rate, GDP growth as well as interest rate. A set of five commercial and development banks listed on Nepal Stock Exchange (NBBL, GBBL, HBL, NABIL and SCBN) over four years (2021/22-2024/25) was used in conducting a sample analysis of panel data regression using a positivist research paradigm and causal-comparative design. The findings show that DPS has a highly significant positive effect on ΔMPS ( 0.68, p < 0.01) and a highly significant negative effect on VOL ( 0.42, p < 0.01), hence supporting signalling theory and the bird-in-the-hand theory. DPR has a positive effect on ΔMPS ( 0.24, p < 0.05) but is not significant on volatility. These relations are greatly moderated by the macroeconomic variables: they are softened by inflation and interest rates and reinforced by GDP growth. The models explain 78.6 percentage of the price variation and 68.4 percentage of volatility variation. These results indicate that the effectiveness of dividend policy depends on the contextual factors, which have significant implications to corporate, investors and policymakers who engage in developing economies.